Eksplorasi Dan Karakterisasi Cendawan Entomopatogen Strain Metarhizium sp. Lokal Di Beberapa Kabupaten Di Kalimantan Timur: Exploration and Characterization of Entomopathogenic Fungi Metarhizium sp. Local In Several Districts In East Kalimantan - Ni’matuljannah Akhsan (Universitas Widya Gama Mahakam, 2021)
Entomopathogenic fungi are microorganisms that can be used as bioinsecticides. The effectiveness of fungi is influenced by the surrounding environment so that it is necessary to explore specific local entomopathogenic fungi. Larva of Tenebrio molitor Linn was used as the insect bait, to isolate the fungi. The Soil for trapping entomopathogenic fungi was taken by purposive sampling from the field of staple food, horticulture, and estate crops in six districts of the East Kalimantan. The observation showed that ten isolates of Metarhizium sp. were very high pathogenicity, five isolates were moderates, and three isolates were very low. The characteristics of Metarhizium sp. isolates grown in GYA medium were 0.25 cm per day of colony growth, initially white colonies, 3-7 days started green from the edges, 14 days the entire colony was dark green. Hyaline hyphae, insulated, rigid conidiophoreser, cylindrical and single-celled conidia. The T. molitor larvae attacked by Metarhizium sp. were stiff in three days after application (daa), grew white hyphae in 6 daa, and grew dark green colony in 9 daa.